Bit-rate sensitivity of filter-bank-based VDSL transmission to timing errors. - Louveaux, J.
The performance degradation of filter-bank-based multicarrier transmission due to timing errors is investigated. The receiver is made of a fractionally spaced linear or decision-feedback equalizer designed for some sampling phase. The actual sampling phase is different and the impact of the difference on the performance is investigated. Sampling phase offset and jitter are considered. Besides, assuming the sampling phase error can be estimated the efficiency of various types of interpolation is investigated
Keywords: Bit-rate sensitivity; Decision-feedback equalizers; Filter-bank-based VDSL transmission; Filter-bank-based multicarrier transmission; Fractionally spaced linear or decision-feedback equalizer; Interpolation; Jitter; Performance degradation; Receiver; Sampling phase error; Timing errors